Synthesis of novel analogues of natural phytohormones and the growth of wheat bioscreening (Experimental biology, 2015)
The paper presents data on the combinatorial synthesis of synthetic plant growth regulators on the basis of aromatic propargyl piperidols and the results of the biological screening rostaktiviruyuschuyu activity in wheat seeds.
Keywords: plant growth regulator; combinatorial synthesi; aromatic propargyl piperidoly; plant protection chemicals; plant hormones; bioscreening; wheat